Informacijsko-komunikacijska (IKT) oprema v splošnih knjižnicah - Bon, Milena (Knjižnica, 2013)
Purpose: The article presents and analyses data about ICT equipment (herein after referred to as ICT) in public libraries and compares them with requirements of some national and international professional guidelines and rules.Methodology / Approach: In 2010 area regional libraries (herein after referred to as regional libraries) collected data on ICT in public libraries in their region resulting in the state-of-the art analysis of a certain region. On the basis of data gathered the Library System Development Centre (LSDC) at the National and University Library presented a state level analysis of the ICT equipment in libraries.Results: It was stated that by increasing the number of computer workstations (herein after referred to as CW) in 2010 the plan of the Resolution of national programme for culture 2008-2011 concerning the number of personal computers was attained. Other ICT equipment was modernised, too. From the point of view of professional guidelines (Standards, 2005) the number of CW is far from being reached. Just over thirty-four per cent (34,35 % or 1.356 CW out of 2.050 CW needed considering the population size and library network) of required CW per 1.000 potential users were recorded. Minimum requirements for the number of CW as recommended in professional rules (Pravilnik o pogojih za izvajanje knjižnične dejavnosti kot javne službe) have not been met in one region only. The state-of-the-art was taken into account not respecting recommendations for the distributed library network organisation as set in the guidelines. Only one region met the requirements regarding the number of CW, however their equipment was outdated. The analysis showed that 43% of CW in public libraries were older than 5 years with outdated software using Microsoft Windows XP operational system leading to serious risks in the next two years. Thus, the upgrading of the 74 % of CW using Windows XP is inevitable. The number of ICT professional staff in 2010 did not meet requirements set in the guidelines, too. According to the guidelines and the number of CW public libraries should employ 65,3 members of ICT professional staff (in 2010: 29). The recommendations of Standards (2005) were reached in more than 41% of libraries sampled. 11 ICT professional staff members were employed in eight out of ten regional libraries.Research limitation: Research was limited to the ICT equipment survey in libraries at the end of 2010 and basic statistical analysis. The survey did not examine compliance to requirements of standards (minimum number of CW) in every local library.Originality/practical implications: Findings of the survey analysis have not been published yet. They can help central regional libraries in planning regional development strategy; they can also aid in making national strategic plans for modernising ICT and serve as the basis for adequate funding of ICT equipment in regions.
Keywords: osrednje območne knjižnice; public libraries; splošne knjižnice; central regional library; area regional library; informacijsko-komunikacijska tehnologija; information and communications technology; information communication equipment; Irkutsk International Airport; IKT; Osrednja območna knjižnica; stats; statistics; statistični podatki; Slovenia; knjižnične mreže; Slovenija